1972
DOI: 10.1085/jgp.60.5.609
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sodium and Potassium on Ouabain Binding by Human Erythrocytes

Abstract: Ouabain binding by the human erythrocyte membrane is reversible, exhibits a high degree of chemical specificity, and can be detected at ouabain concentrations as low as 1 X 10-1 0 M. The relation between ouabain binding and ouabain concentration can be described by a rectangular hyperbola permitting determination of the maximal binding (Bma) and the ouabain concentration at which ouabain binding is half-maximal (KB). Reducing the external sodium concentration increased KB, while reducing the external potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
60
1
1

Year Published

1975
1975
1985
1985

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 10 publications
(16 reference statements)
18
60
1
1
Order By: Relevance
“…It is known that these steroids act on the outside of the membrane (Hoffman, 1966;Perrone and Blostein, 1973), and that the ionic composition of the external medium affects the rates at which the binding of the steroid and the inhibition of the pump occur (Hoffman, 1966;Beaug~ and Adragna, 1971;Gardner and Conlon, 1972;Sachs, 1974;Gardner and Frantz, 1974). One experimental approach to this problem has been to study the effects of monovalent cations on the steroid binding in comparison with the effects of these same ions on the pump rate.…”
mentioning
confidence: 99%
“…It is known that these steroids act on the outside of the membrane (Hoffman, 1966;Perrone and Blostein, 1973), and that the ionic composition of the external medium affects the rates at which the binding of the steroid and the inhibition of the pump occur (Hoffman, 1966;Beaug~ and Adragna, 1971;Gardner and Conlon, 1972;Sachs, 1974;Gardner and Frantz, 1974). One experimental approach to this problem has been to study the effects of monovalent cations on the steroid binding in comparison with the effects of these same ions on the pump rate.…”
mentioning
confidence: 99%
“…In intact cells a reciprocal relationship between the binding of ouabain to erythrocytes and the concentration of potassium has been demonstrated (Gardner & Conlon, 1972); a similar relationship between the cellular binding of ouabain and potassium has been demonstrated in myocardial cells (Baker & Willis, 1972;McCall, 1979).…”
Section: Introductionmentioning
confidence: 76%
“…In these studies it was shown that K+ inhibited the binding of cardiac glycosides in various membrane preparations exhibiting Na+, K+ ATPase activity. The relationship between ouabain receptor affinity and K+ was found to be hyperbolic by Gardner & Conlon (1972) (Figure 4). Moreover, the antagonistic effect ofK + on glycoside binding was dissociated from its effect on the inotropic actions, even though it was shown (Ebner, 1984) (Figure 8).…”
Section: Discussionmentioning
confidence: 98%
“…In various preparations the binding of cardiac glycosides was found to be proportional to the Na+ concentration (Baker & Willis, 1972;Gardner & Conlon, 1972;Lindenmayer et al, 1973;Erdmann & Schoner, 1973;Inagaki etal., 1974;Hobbs & Dunham, 1978;Furukawa et al, 1980). However, the reduction of ouabain receptor affinity cannot be the sole mechanism by which Na+ withdrawal reduces the inotropic effect of cardiac glycosides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation